Tumor-resident Malassezia can promote hepatocellular carcinoma development by downregulating bile acid synthesis and modulating tumor microenvironment - Weixi Shen; Zhihong Li; Lei Wang; Qi Liu; Renjie Zhang; Yuhua Yao; Zhicheng Zhao; Lei Ji (Scientific Reports)
Abstract Bacterial dysbiosis coincides with the carcinogenesis in malignancies such as lung and colon cancer, and has recently been suggested to involve in the pathogenesis of hepatocellular carcinoma (HCC). However, the mycobiome has not yet been definitively linked to liver tumorigenesis. Here we showed that the microbiota composition of HCC tumors was distinct from that of the normal adjacent to tumor (NAT) on the basis of richness and beta-diversity indices. Specifically, the fungal community that infiltrated HCC tumors was markedly enriched for Malassezia spp. and genus Malassezia in tumors was substantially more abundant than that in NAT. We also discovered that the relative abundance of genus Malassezia was strongly correlated with the tumor microenvironment (TME) signatures, including stromal and immune components. In addition, tumor-resident Malassezia could inhibit bile acid synthesis by downregulating the expression level of CYP7 A1 and CYP27 A1. To improve clinical usability, we developed a set of Malassezia-related genes, called Malassezia.Sig, which could accurately predict patient survival. Collectively, our work shows that tumor-resident Malasseiza may promote HCC progression by downregulating bile acid synthesis and modulating the TME, although more studies are needed.